Revealing weak grain refinement and atypical extrusion texture of Al–Mg–Si alloy miniature complex hollow profile extruded at ultra-large extrusion ratio - Yongda Liu; Qingwen Yun; Ying Dong; Haichuang Li; Xu Huang; Guangyu Ma; Zhichao Li; Guangjun Dong; Jun Xiong; Debin Shan; Bin Guo; Jie Xu (Journal of Materials Research and Technology)
Porthole die extrusion of Al–Mg–Si alloy miniature complex hollow profile with ultra-large extrusion ratio and micro features was found to exhibit unique characteristics, including weak grain refinement and atypical extrusion textures. The key findings indicated that even at low extrusion temperatures ranging from 400 °C to 420 °C, the grain refinement remained weak with the average grain size of the profile decreasing from 61.8 μm to 30.0–40.9 μm. It was attributed to the ultra-large strain caused by an ultra-large extrusion ratio of 137, inducing premature high degree of dynamic recrystallization (DRX) in the weld chamber and subsequent secondary extrusion of the prematurely formed DRXed grains with complex deformation history, involving secondary extrusion, dynamic recovery, dynamic/static recrystallization and abnormal grain growth processes. The preferred grain orientation of the profile was also severely weakened, with atypical extrusion textures emerging. Near <100> fiber texture dominated in the thick-walled area, while near shear texture formed in the micro rib. The complex deformation history caused a deviation history from the ideal <100> fiber texture, and strong friction in the micro rib led to severe shear deformation, characterized by extremely strain and ultra-high strain rate, resulting in the formation of near shear texture.